THE RELATIONSHIP BETWEEN GRAMMATICAL CATEGORIES AND THE TEMPORAL INTERPRETATION OF THE RUSSIAN GERUND AND THE SPANISH NON-PERIPHRASTIC GERUND (Philological Studies, 2022)
The article contrasts the Russian gerund (the deepričastie form) and the Spanish non-periphrastic gerund from a morphosyntactic and semantic point of view. The foundation of the research is the converb, a non-finite verb form that expresses adverbial subordination. Based on this definition, we first try to ascertain whether the Russian gerund and the Spanish non-periphrastic gerund can be considered a part of the aforementioned category. Furthermore, we focus on the category of verb tense, which is divided into an absolute and relative tense, thus  we analyze how the Russian gerund and the Spanish non-periphrastic gerund express temporal relations. Special attention is paid to the description of the expression of aspect in Russian and Spanish and to researching how differences in the expression of this category affect the semantic interpretation of gerunds. Based on the representative examples taken from a parallel Russian-Spanish corpus, we finally analyze the primary adverbial meanings of Russian and Spanish gerunds, i.e., temporal meanings of simultaneity, anteriority, and posteriority. Using contrastive analysis, we conclude that due to their aspectual properties, the Russian gerund and the Spanish non-periphrastic gerund as converbs are not entirely the same, which is why they do not always match when expressing temporal relations.